Training Senior High School English Teachers in Developing Listening Assessment - Nur Habibah (IJET (Indonesian Journal of English Teaching), 2017)
The ceaseless assessment ignorance, ineffective practices, even indisposition to assess listening skills among English teachers are prevalent due to the complexity of providing spoken texts, the impractical implementation, not to mention the little concern regarding teachers’ assessment development. One possible way to address the problem is to improve teachers’ knowledge and skills as well as encourage them to develop listening assessment through a more specific, practical and comprehensive assessment teacher training. The present study tries to train nine English fellow teachers of Senior High Schools of Amanatul Ummah in Mojokerto and Surabaya. The training focuses on the knowledge of basic concept of assessment, principles of designing a good assessment, basic types of listening assessment, tips in selecting authentic materials and the skills involving the trainee teachers’ practices in developing listening assessment. Data were collected through pre and post-tests, pre-lesson notes, worksheets, reflective journal entries, and pre and post-projects. The finding shed light on the teachers’ changes in knowledge, skills, and disposition to develop listening assessment during the process and afterwards.